Lancers for the King : a Study of the Frontier Military System of Northern New Spain, with a Translation of the Royal Regulations of 1772 - Brinckerhoff, Sidney B. (Arizona Historical Foundation)
Historia militar del norte de México a finales del siglo XVIII, en donde los militares españoles tenían el objetivo de expander el territorio hacia lo que ahora es Estados Unidos.